Organizational Forms of Teaching as a Component of Methodical System of Formation Informative Competencies of Primary School Teachers - Valentyna Baranovska (Pedagogical Discourse, 2015)
The article deals with new approaches to organization of informative future teachers’ training on competency-based grounds that providing harmonious, balanced and appropriate mix of traditional and modern information and communication technology training of future teachers of primary school. The structure of system of the informative competence of the future teachers provides scientific foundation of methodical system of formation informative competencies of the future primary school teachers and the relationship of its components: purpose, content, methods, tools and organizational forms of learning.It is determined that the content of education, purpose and objectives, teaching methods are implemented through organizational forms. The organization forms of education means the series of external conditions which contain organization and learning process.The educational process in higher education establishments is conducted in the following forms: training sessions; independent work; practical training; control tests. It should be taken into consideration that teaching and educational technology – the systems of methods, tools and techniques that are used to achieve the educational and pedagogical goals, their current level is largely characterized by the possibilities of using the modern information and communication systems, multimedia and others.